Comparison of Efficacy of Trunatomy Irrigation Needle, Sonic Irrigation Technique, and Ultrasonic Irrigation Technique in Retrievability of Rc Cal, Metapex, and Bio C Temp from Root Canals: An In-Vitro CBCT Analysis - Ajay Nevil; Faisal M. A. Gaffoor; Rethi Gopakumar; C. Sabari Girish; N. C. Sajeena; V. N. Anoop (Journal of Pharmacy and Bioallied Sciences)
Introduction: Most of the irrigant activation systems commonly used were unable to completely remove intracanal medicament placed within the root canal system. With emphasis to this clinical hurdle, the aim of the study was to compare the efficacy of Trunatomy irrigation needle, Ultrasonic and sonic activation techniques in the retrievability of intracanal medicaments like Rc Cal, Metapex and Bio C Temp. Materials and Methods: Sixty-three mandibular premolar teeth with straight single root canal were selected and filled with Rc Cal, Metapex and Bio C Temp and were activated using different techniques like, Trunatomy irrigation needle, sonic irrigation technique and ultrasonic irrigation technique. Volumetric analysis of remaining intracanal medicament was assessed using CBCT. Conclusion: None of the irrigants used were able to completely remove intra-canal medicament from root canal. Sonic activation technique showed significant removal efficacy than ultrasonic and Trunatomy irrigation needle.